Low education, more frequent of seizure, more types of therapy, and generalized seizure type decreased quality of life among epileptic patients (Faculty of Medicine Universitas Indonesia, 2007)
Persons with chronic disease such as epilepsy, where a cure is not attainable and therapy may be prolonged, quality of life (QoL) has come to be seen as an important goal. The objective of this study was to identify scores of quality of life (QoL related to clinical factors. A cross-sectional study using QOLIE-31 instrument to identify quality of life among ambulatory epileptic patients at Epileptic Clinic of Department of Neurology-Cipto Mangunkusumo Hospital. Samples were taken consecutively from August 2005 to December 2005. Several demographic data as well as clinical were collected. QOLIE-31 components consisted of seizure worry, overall quality of life, emotional well-being, energy/fatigue, cognitive function, medication effect and social function. We found among 145 subjects the total score of QOLIE-31 ranged from 28-95 (mean = 67.6; standard of deviation = 14.55). The total score of QOLIE-31was corelated with low education, more frequent of seizures, antiepileptic drug politherapy and type of generalized seizure. antiepileptic drug politherapy was the most dominant risk factor for lowering total score of QOLIE-31. Our finding was in accordance with previous studies in India, Georgia, South Korea. In additioin we found that education was also a risk factor for total score of QOLIE-31. (Med J Indones 2007; 16:101-3) Keyword: epilepsy, quality of life, QOLIE-31, risk factors